2013
DOI: 10.1620/tjem.230.241
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Sector Reforms in Reducing Disparities in Utilization of Skilled Birth Attendants in Tanzania

Abstract: Improving maternal health is a Millennium Development Goal adopted at the 2000 Millennium Summit of the United Nations. As part of the improving maternal health in Tanzania, it has been recommended that skilled birth attendants be present at all births to help reduce the high maternal mortality ratio. However, utilization of these attendants varies across socio-economic groups. The government of Tanzania has repeatedly attempted to carry out health sector reforms (HSRs) to alleviate disparities in health servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Tanzania has seen a modest increase in the proportion of births occurring in health facilities; from 43.5% in 1999 to 50.1% in 2010 [7], but wide socio-economic inequalities in the utilization of skilled birth attendance exist [11]. To reduce maternal mortality, the Tanzanian government proposed scaling-up the availability of basic emergency obstetric and newborn care services at dispensaries and health centres, and improving the ability of rural health centres to perform caesarean sections and blood transfusions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tanzania has seen a modest increase in the proportion of births occurring in health facilities; from 43.5% in 1999 to 50.1% in 2010 [7], but wide socio-economic inequalities in the utilization of skilled birth attendance exist [11]. To reduce maternal mortality, the Tanzanian government proposed scaling-up the availability of basic emergency obstetric and newborn care services at dispensaries and health centres, and improving the ability of rural health centres to perform caesarean sections and blood transfusions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Table reports the characteristics of the articles selected for review. Sixteen different studies were identified, with the earliest one published in 2003 and the most recent one published in 2016 . The selected studies were situated in Latin America ( n = 8), Asia ( n = 5), Africa ( n = 2), and multiple countries ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The studies used cross‐sectional analysis ( n = 3) or longitudinal analysis ( n = 13); of the latter, 11 were based on panel data and 2 were based on repeated cross‐sectional. Among all studies, only 4 employed individual‐level analysis using individual or household data from survey data, whereas the remaining studies used the ecological analysis approach. The analytical methods that were used in the studies varied from fixed effects, modified difference‐in‐difference, instrumental variable estimation, multilevel modeling, and regression‐based analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations